Gonad development and size at maturity of the male mud crab Scylla paramamosain (Forsskål, 1755) in a tropical mangrove swamp - Islam, Md. Sherazul; Kurokura, Hisashi (Journal of Fisheries, 2013)
The reproductive traits and size at sexual maturity of the male mud crab Scylla paramamosain were investigated in Pak Phanang mangrove swamps, Thailand. Samples were taken seven times from the local middlemen mud crab traders during June 2006 to January 2008. Gonad development was determined based on histological appearance that was classified into three stages: 1) Immature (Spermatogonia), 2) Maturing (Spermatocytes) and 3) Mature (Spermatids and Spermatozoa). Among the sample population, the highest 72% was under gonad development stage I, whereas mature stage III was only 12%. The size at first maturity was estimated by the external allometric growth and histological observation of gonad. The size at which 50% of individuals attain sexual maturity was estimated by the two mathematical models such as probit analysis and logistic curve. The mean size at first sexual maturity and 50% maturation of male S. paramamosain were 96 mm and 109 mm internal carapace width (ICW) which revealed that 88% individuals were immature. The present result suggested that the minimum legal size of male S. paramamosain capture should be >110 mm ICW.